(untitled) (AYUSHDHARA, 2022)
There are group of disorder that develops as complication of dyslipidaemia which can be categorise under Santarpanjanya vikaras. Modernisations have certainly made our live easier, but they have led many of us to adopt more sedentary and luxurious life. Wrong eating habits, indulgence in drinking, smoking, alcohol consumption, drug abuse, malnutrition, stress and many more are the presentation of unhealthy lifestyle, which nowadays is considered as good and dominant form of lifestyles. Due to more stress and decreased physical activity various sedentary lifestyle disorders like diabetes mellitus, hypertension, dyslipidaemia, obesity, thyroid disorder, PAD etc develops. The incidence of these lifestyle disorder associated with cardiovascular diseases is high on the rise. This study mainly focuses on the facts and management of Santarpanjanya vikaras occur as result of dyslipidaemia (lifestyle emerging condition).